Exploring nursing students' need for social presence and its relevance to their learning preferences - Joseph Grech (Wiley, 2022)
Abstract Aim To explore nursing students' need for social presence in online learning, looking at its relevance to the adopted sensory modality learning styles. Design A qualitative descriptive design. Methods Two semi‐structured online focus groups were held with five second‐year and seven third‐year undergraduate nursing students, purposively recruited from the Malta College of Arts, Science and Technology. Using a structured guide based on the Social Presence Model, participants were asked about their perceived need for social presence (a construct used to understand online interactions), and its relevance to their learning preferences using the VARK (Visual, Aural/Auditory, Read/write and Kinesthetic) learning styles. Results Despite varying learning preferences, all participants remarked on the need for social presence. Social presence was required for their perceived learning and for actively participating in online lectures. Several participants expressed the need for social presence for a collaborative constructivist learning experience, drawing on their diverse learning styles for a better learning experience.